Interprofessional Approaches to Heavy Metal Exposure Assessment and Management - Alazmi, Mohammad Hssin S; Sulaiman Mohammed Dhaher Alsharari; Saida Yahia Ali Ghzwani; Saad Hamoud Qahtan Alshehri; Khulood Majed Hamoud Almutairi; Mohammed Abdulrahman M Abobaker; Mohammed Eid S Aljohany; Fahad Abdullah Sudan Almutairi; Ali Abdulaziz Alrayes; Ibrahim Ahmed Khabrani; Kadhem Yousef Al Sultan; Ahmad Yahya Qasem Ghazwani; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Heavy metal exposure, stemming from both environmental and occupational sources, poses a significant global health risk. While some metals are essential in trace amounts, others like lead, arsenic, and mercury are toxic, causing multisystem damage through mechanisms like oxidative stress and enzyme inhibition. Diagnosis is challenging due to nonspecific symptoms that mimic common diseases. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This comprehensive review aims to detail the interprofessional approaches required for the effective assessment and management of heavy metal toxicity. It synthesizes information on etiology, pathophysiology, diagnostic testing, and collaborative care strategies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review outlines the critical procedures for accurate diagnosis, including the selection of appropriate biological specimens (blood, urine, hair) based on the metal's pharmacokinetics and the timing of exposure. It emphasizes advanced analytical techniques like Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and the importance of rigorous quality control to prevent contamination and ensure result reliability. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Accurate diagnosis hinges on correlating a plausible exposure history with consistent clinical symptoms and confirmatory laboratory testing. The clinical significance of test results must be interpreted within the context of population reference ranges and individual patient factors, as even low-level exposures can be harmful to vulnerable groups. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective management of heavy metal toxicity necessitates a coordinated, interprofessional effort. This involves clinicians, nurses, laboratory personnel, and toxicologists working together to ensure accurate diagnosis, guide interventions like chelation therapy, implement exposure mitigation, and protect public health.